Eating disorders: A 25-year perspective. Issue 5 (20th October 2017) - Andersen, Arnold; Foreyt, John; Maine, Margo; Cohn, Leigh
ABSTRACT: I founded Eating Disorders: The Journal of Treatment & Prevention 25 years ago, and its character, reputation, and success are highly attributable to Arnold Andersen, John Foreyt, and Margo Maine, the three original senior editors, whose perspectives follow in this article. Having made the decision to retire from the journal, I asked the senior editors to transition to the emeritus board along with me, which I explain further in my own Last Word, "Goodbye, Eating Disorders, " in this volume (Cohn, 2017). Over our 25 years of collaboration, the senior editors have acquired unique insights into the evolution of the eating disorders field; so, I asked them to contribute retrospective essays in which they also look forward within their primary areas of expertise—presented here in alphabetical order. – Leigh Cohn, Editor-in-Chief